Interoptic, Trans-lamina Terminalis, Opticocarotid Triangle, and Caroticosylvian Windows From Mini-Supraorbital, Frontomedial, and Pterional Perspectives: A Comparative Cadaver Study With Artificial Lesions - Adib, Sasan Darius; Herlan, Stephan; Ebner, Florian H.; Hirt, Bernhard; Tatagiba, Marcos; Honegger, Juergen (Frontiers in Surgery, 2019)
Abstract Introduction: Mini-supraorbital (MSO) and pterional (PT) approach have been compared in a number of studies focusing on the treatment of aneurysms, craniopharyngiomas and meningiomas. The goal of this study was to analyze the surgical exposure to different artificial lesions through interoptic (IO), trans-lamina terminalis (TLT), opticocarotid triangle (OCT) and caroticosylvian (CS) window from MSO, frontomedial (FM) and PT perspective. Methods: The MSO, PT and FM approach were performed sequentially in two fixed cadaver heads. Three colored spheres were placed around the optic chiasm: 1. Between the optic nerves; 2. Between the optic nerve and the internal carotid artery; 3. Between the internal carotid artery and the oculomotor nerve. The surgical exposures to these structures by using IO-, TLT-, OCT- and CS-window were compared. Results: 1. IO window: From MSO and PT approach the total surgical exposure mainly allows visualization of contralateral lesions. The FM approach was superior for exploration of both sides of the area between the optic nerves. 2. TLT pathway: MSO and PT approach mainly expose the contralateral third ventricle wall. 3. OCT window: PT approach allows to expose a larger part of the sphere between the optic nerve and the internal carotid artery than the MSO approach. 4. CS window: PT approach allows a better exposure of lateral structures such as the oculomotor nerve and of the medial prepontine area in comparison to the MSO approach. Conclusion: Simulation of the surgical situation with artificial lesions is a good model for comparing surgical perspectives and for analyzing feasibility of lesion exposure and resection.